V World Social Forum, advance or retreat? - de Souza, Helena (2016)
This article reviews the origins and main objectives of the World Social Forum. It analysis problems related to the World Social Forum's organization and Development, focusing specially on those criticisms related to its concrete results. The author proposes the need for a radical change in the anti-imperialist, anti-neoliberal alternatives.